2016
DOI: 10.1590/1414-431x20154890
|View full text |Cite
|
Sign up to set email alerts
|

Effects of continuous vs interval exercise training on oxygen uptake efficiency slope in patients with coronary artery disease

Abstract: The oxygen uptake efficiency slope (OUES) is a submaximal index incorporating cardiovascular, peripheral, and pulmonary factors that determine the ventilatory response to exercise. The purpose of this study was to evaluate the effects of continuous exercise training and interval exercise training on the OUES in patients with coronary artery disease. Thirty-five patients (59.3±1.8 years old; 28 men, 7 women) with coronary artery disease were randomly divided into two groups: continuous exercise training (n=18) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 23 publications
4
41
2
Order By: Relevance
“…The authors of seventeen studies [10, 12, 13, 2023, 2529, 31, 33, 3537] involving 611 patients reported on peak heart rate following INTERVAL and CONTINUOUS. A random-effects model revealed no significant difference between groups (MD 0.97 bpm, 95% CI −2.19 to 4.12 bpm, p = 0.55).…”
Section: Resultsmentioning
confidence: 99%
“…The authors of seventeen studies [10, 12, 13, 2023, 2529, 31, 33, 3537] involving 611 patients reported on peak heart rate following INTERVAL and CONTINUOUS. A random-effects model revealed no significant difference between groups (MD 0.97 bpm, 95% CI −2.19 to 4.12 bpm, p = 0.55).…”
Section: Resultsmentioning
confidence: 99%
“…30,31 Globally, in spite of a reduced total volume of physical activity, IATP-R induced also enhancement in aerobic capacities of similar extends to which previously reported with common IATP. Thus, in seniors, Coker et al, 32 Foster et al, 33 Perini et al, 24 and Vogel et al 10 reported a significant improvement in VO 2peak of 14%-17% after 9-12 week of IATP. This magnitude of VO 2peak enhancement was also similar to those measured after medium-(ie, 14-24 weeks) 34,35 and long-term (ie, >24 weeks) 36 37 Furthermore, VO 2peak is also considered as the most powerful predictor of mortality compared to other wellestablished risk factors.…”
Section: Discussionmentioning
confidence: 96%
“…21 The great adherence rate reported with IATP-R was much higher than those usually reported with common IATP. [22][23][24][25] It was explained by the design of the program that was supervised and personalized. These criteria are known to be more effective in reducing the risk of injury and in improving performance among seniors compared to home-based or un-supervised programs.…”
Section: Discussionmentioning
confidence: 99%
“…Although encouraging, the data supporting the prognostic value of OUES is limited to date due to a lack of appropriately powered prospective studies and warrants further investigation. The OUES displays prognostic value in patients with HF [49][50][51] and coronary artery disease (CAD) [52,53] and has been shown to be responsive to physical training in patients with CAD [54,55].…”
Section: Oxygen Uptake Efficiency Slopementioning
confidence: 99%